Probing chitosan and phospholipid interactions using Langmuir and Langmuir-Blodgett films as cell membrane models - Pavinatto, Felippe J (Langmuir : the ACS journal of surfaces and colloids, 2007)
The interaction between chitosan and Langmuir and Langmuir-Blodgett (LB) films of dimyristoyl phosphatidic acid (DMPA) is investigated, with the films serving as simplified cell membrane models. At the air-water interface, chitosan modulates the structural properties of DMPA monolayers, causing expansion and decreasing the monolayer elasticity. As the surface pressure increased, some chitosan molecules remained at the interface, but others were expelled. Chitosan could be transferred onto solid supports alongside DMPA using the LB technique, as confirmed by infrared spectroscopy and quartz crystal microbalance measurements. The analysis of sum-frequency vibration spectroscopy data for the LB films combined with surface potential measurements for the monolayers pointed to chitosan inducing the ordering of the DMPA alkyl chains. Furthermore, the morphology of DMPA LB films, studied with atomic force microscopy, was affected significantly by the incorporation of chitosan, with the mixed chitosan-DMPA films displaying considerably higher thickness and roughness, in addition to chitosan aggregates. Because chitosan affected DMPA films even at pressures characteristic of cell membranes, we believe this study may help elucidate the role of chitosan in biological systems